Could Ossification of the Achilles Tendon Have a Hereditary Component?. (30th April 2013) - Cortbaoui, Chawki; Matta, Jihad; Elkattah, Rayan
Abstract : Ossification of the Achilles tendon (OTA) is an unusual clinical condition. It is characterized by the presence of an ossified mass within the fibrocartilaginous substance of the Achilles tendon. The etiology of the ossification of the Achilles tendon is unknown. Review of the literature suggests that its etiology is multifactorial. The major contributing factors are trauma and surgery with other minor causes such as systemic diseases, metabolic conditions, and infections. To our knowledge, no previous reports suggest any genetic/hereditary predisposition in OAT. We report 3 siblings who have OAT with no history of any of the aforementioned predisposing factors. Could OAT have a hereditary component as one of its etiologies?